2021
DOI: 10.3390/polym13213614
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Thermal Insulating Polyimide/Cellulose Nanocrystal Composite Aerogels with Low Dimensional Shrinkage

Abstract: Polyimide (PI)-based aerogels have been widely applied to aviation, automobiles, and thermal insulation because of their high porosity, low density, and excellent thermal insulating ability. However, the fabrication of PI aerogels is still restricted to the traditional molding process, and it is often challenging to prepare high-performance PI aerogels with complex 3D structures. Interestingly, renewable nanomaterials such as cellulose nanocrystals (CNCs) may provide a unique approach for 3D printing, mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 54 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…29 Hence, such structure and property differences between axial and radial directions of anisotropic aerogel materials provide promising candidates for microelectronics, thermal insulation, and electromagnetic interference shielding applications. 27,29,32,40 Nanofillers with low thermal conductivity such as silica, 11,13 glass fiber, 41 cellulose nanocrystal, 42 attapulgite, 43 and halloysite 44 are also incorporated to facilely fabricate heatinsulated PI composite aerogels. However, maintaining low shrinkage and tuning pore morphology remain a recurring challenge in such an area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Hence, such structure and property differences between axial and radial directions of anisotropic aerogel materials provide promising candidates for microelectronics, thermal insulation, and electromagnetic interference shielding applications. 27,29,32,40 Nanofillers with low thermal conductivity such as silica, 11,13 glass fiber, 41 cellulose nanocrystal, 42 attapulgite, 43 and halloysite 44 are also incorporated to facilely fabricate heatinsulated PI composite aerogels. However, maintaining low shrinkage and tuning pore morphology remain a recurring challenge in such an area.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofillers with low thermal conductivity such as silica, , glass fiber, cellulose nanocrystal, attapulgite, and halloysite are also incorporated to facilely fabricate heat-insulated PI composite aerogels. However, maintaining low shrinkage and tuning pore morphology remain a recurring challenge in such an area.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 below represents the two techniques adopted for fabricating various shapes and sizes of samples. This study suggested that SLA and DIW could be used to fabricate efficient thermal insulating polymer composites 49 …”
Section: Development Of Thermal Insulating Materials Using 3d Printingmentioning
confidence: 91%
“…This study suggested that SLA and DIW could be used to fabricate efficient thermal insulating polymer composites. 49 In a recent study, polyamide was used to fabricate 3D-printed gyroid structured objects through selective layer sintering 3D printing. B. Anwajler carried out this experimental work.…”
Section: Geopolymeric Foam Was Essentially Studied and Used By Hussammentioning
confidence: 99%
“…Recent advances in multi-material 3D printing present a potential extension of the product design beyond complex geometries, while functional, single-step manufacturing processes can be exploited by utilizing custom composite materials suitable for multifactorial applications. The fused filament fabrication (FFF) technique is of low cost with a large range of feedstock materials suitable for a wide range of 3D printing applications [ 4 , 5 ]. Thermoplastic materials, such as polylactic acid (PLA) and polyamide (PA) [ 6 ], can be melted and extruded as a strand through a nozzle in a line by line and layer by layer manner in FFF, and the extruded material (thermoplastic strands) rapidly solidifies and adheres with the surrounding material, which is especially useful for complex design and advanced functionality of smart products [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%